Humic acid inhibition of hydrolysis and methanogenesis with different anaerobic inocula. (October 2018) - Yap, S.D.; Astals, S.; Lu, Y.; Peces, M.; Jensen, P.D.; Batstone, D.J.; Tait, S.
Highlights: Humic acid (HA) inhibition resilience differed with the inoculum source. Experimental results below 5 gHA L −1 support a threshold inhibition mechanism. HA < 5 g L −1 led to a time lag, but cellulose hydrolysis rate was unaltered after it. HA did not affect protein digestion up to 5 gHA L −1 . Methanogenesis was inhibited at 20 gHA L −1 . Abstract: There is increasing evidence that humic acid (HA) is hampering the performance of anaerobic digesters treating animal manures and thermally-hydrolysed waste activated sludge. In the present study, HA inhibition and inhibition resilience was examined for hydrolysis (carbohydrate and protein) and acetotrophic methanogenesis with four distinct full-scale anaerobic inocula. The aim was to further understand HA inhibition and to explore potential relationships between microbial factors and inhibition resilience. For two of the four tested inocula, cellulose degradation showed a start-up delay that lengthened as HA concentration increased from 0 to 2 g L −1 . This inhibition was reversible because, after the initial delay, subsequent hydrolysis rates and methane yields were not significantly influenced by HA concentration. Cellulose hydrolysis results at HA concentrations below 2 g L −1 support a threshold inhibition mechanism, i.e. HA complexes with hydrolytic enzymes preventing them from binding with cellulose, but once all the HA had been complexed, enzymes subsequently released are free to bind with cellulose. Inocula with higher cellulose hydrolytic activity were less affected by HA inhibition, suggesting a potential link between HA inhibition resilience and microbial activity. However, above 5 gHA L −1, cellulose hydrolysis rates decreased with increasing HA concentration; indicating that the mechanisms of inhibition may change depending on some threshold HA concentration. Protein hydrolysis and acetotrophic methanogenesis were less susceptible to HA inhibition than cellulose hydrolysis, since signs of inhibition were only observed above 5 gHA L −1 . Acetotrophic methanogenesis was partially inhibited at 10 gHA L −1 and completely inhibited at 20 gHA L −1 . These results further support that HA inhibition is selective towards particular enzymes.